2016
DOI: 10.1039/c5cy01462j
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly hydrogenation of aromatic aldehyde compounds by tandem dehydrogenation of dimethylamine-borane in the presence of a reduced graphene oxide furnished platinum nanocatalyst

Abstract: An easy and effective synthetic method has been developed for the reduction of aldehyde compounds in the presence of monodisperse Pt(0)/TPA@rGO NPs as the catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Also demonstrated by this technique are representative atomic lattice fringes. Finally, it was observed that the nominal range value of Pt (111) (0.228 nm) was in the same crystal range (0.228 nm) as the characterized Pt nanoparticle 31 .…”
Section: Resultsmentioning
confidence: 72%
“…Also demonstrated by this technique are representative atomic lattice fringes. Finally, it was observed that the nominal range value of Pt (111) (0.228 nm) was in the same crystal range (0.228 nm) as the characterized Pt nanoparticle 31 .…”
Section: Resultsmentioning
confidence: 72%
“…As a reference, the C 1s peak was used at 286.4 eV and the correct binding energy was determined (± 0.3 eV) in all XPS spectra of the prepared materials. 39,40…”
Section: Resultsmentioning
confidence: 99%
“…The shift of the binding energy of nickel to the 2p 3/2 peak indicates the alloying of nickel with palladium at a low energy. 39,40…”
Section: Resultsmentioning
confidence: 99%
“…2-(2-Furanylmethylene) malononitrile (26) was obtained in quantitative yields and in a short time using furan-2-carbaldehyde (25), which is heteroaromatic aldehyde (Table 2, entry 13). On the other hand, this reaction was carried out with aliphatic aldehydes to compare with aromatic aldehydes.…”
Section: Resultsmentioning
confidence: 99%